Microstructure and mechanical properties of Tungsten and Tungsten-Tantalum thin film deposited RAFM steel. (23rd February 2020) - Konuru, S. Lakshmi Kanth; Umasankar, V.; Sarkar, Biswanath; Sarma, Arun
ABSTRACT: Tungsten (W) for its high irradiation behaviour is being studied globally as a potential plasma-facing material. However, thermo-mechanical fatigue caused by high temperature in the fusion process poses a great challenge for the materials engineers. Tungsten, known for its high stiffness and sputtering threshold, has a typical Ductile to Brittle Transition Temperature (DBTT) at 600K. Due to the DBTT of W, stresses raised by thermal fluctuations generate cracks and failure of material occurs. To overcome this challenge, nanostructured composite tungsten–tantalum (W–Ta) thin film has been deposited on Reduced Activation Ferritic Martensitic (RAFM) steel by RF magnetron sputtering process. The secondary phase of Ta in the W matrix has been found to reduce the surface hardness at room temperature. Effects of RF power, substrate temperature and Ta percentage in W matrix have been considered in this study. Various thin-film properties viz adhesion, microstructure and hardness have been studied and analysed in this report.